Pengaruh Pendekatan Kontekstual terhadap Kemampuan Pemecah Masalah Matematika pada Materi Bangun Ruang Sisi Lengkung - Laili, Dini Nur; sari, Liliyana Indah Puspita; Adawiya, Robiatul (Indonesian Journal of Elementary Education and Teaching Innovation, 2024)
This research aims to evaluate the effect of a contextual approach on students' mathematical problem solving abilities in curved geometric shapes. The literature review (SLR) study method was used to analyze 6 scientific articles relevant to the research topic. This research identifies themes and patterns that emerge regarding the influence of a contextual approach on students' mathematical problem solving abilities. The results of the analysis show that the application of the contextual approach has a positive influence on students' mathematical problem solving abilities. Comparison table of scores for the experimental group achieved higher achievement than the control group. Data visualization graphs also reinforce these findings. The conclusion of this research confirms that the application of a contextual approach has a positive impact on solving mathematical problems in curved geometric shapes. The implications of these findings can be a guide for educators and researchers to enrich mathematics learning strategies by integrating everyday life contexts into geometry teaching